A computer intensive method for choosing the ridge parameter - Karsten Lübke; Irina Czogiel; Claus Weihs (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2004)
In this paper we describe a computer intensive method to find the ridge parameter in a prediction oriented linear model. With the help of a factorial experimental design the method is tested and compared to a classical one.
Keywords: 519; Ridge Regression; Experimental Design; Prediction model; Generalized Cross Validation